STRUKTUR PASAR INDUSTRI PERBANKAN INDONESIA: ROSSE-PANZAR TEST - Moh Athoillah (Journal of Indonesian Applied Economics, 2010)
The purpose of  this  research  is  to  determine how  the market  structure of banking industry  in  Indonesia. The research using Rosse-Panzar Test  (PR) methods. Using panel  data  of  10  banks  in  Indonesia which  has  the  largest asset  ratings,  this PRapproach will produce H-Stat value which  is  the sum of  three main coefficients ofbanking inputs (labor, capital and funds). With H-Stat valued at 0.931 can be con-cluded that the Indonesian banking industry into the category of monopolistic mar-ket.